Implementation of the Merdeka Curriculum in Al-Qur'an Hadith Learning at Madrasah Aliyah - Ridha, Zaifatur; Sabariah, Hayatun; Maulana, Irga (Faculty of Tarbiyah Universitas Islam Tribakti Lirboyo Kediri, 2024)
Indonesia's curriculum reform has established the Merdeka Curriculum. Every teacher must prioritize students' freedom, independence, and creativity in implementing it. The research aims to explore the implementation of the Merdeka Curriculum in Al-Qur'an Hadith learning at Madrasah Aliyah Negeri 1 Langkat. The method used is qualitative research. Data collection techniques use observation, interview, and documentation methods. The study found that Al-Quran Hadith learning has used the Merdeka Curriculum learning materials. Teachers also adapt their teaching methods to student needs and interests, identifying strengths and weaknesses. One of the learning methods used in the learning process is project-based learning, which is used to improve critical thinking skills, foster student initiative in working, motivate, and develop group interpersonal relationships. It has an impact on improving student engagement and enthusiasm for learning. This study concluded that the Merdeka curriculum is fully implemented. That emphasizes flexible learning activities, project-based learning, and student-centered approaches and focuses on developing students' competencies.